Case Report: MRSA sepsis after pediatric traumatic pseudoaneurysm - Zhang, Xiongfeng; Zhao, Hua; Yang, Qingtian (Frontiers in Pediatrics, 2025)
Pediatric vascular injuries are rare and present unique clinical challenges due to differences in vessel size, injury patterns, and long-term outcomes compared with adults. We report the case of an 11-year-old boy who developed a ruptured and infected superficial femoral artery pseudoaneurysm following closed blunt trauma, which was further complicated by sepsis and necrotizing fasciitis. The patient underwent urgent surgical repair with autologous great saphenous vein patch angioplasty, combined with extensive debridement of necrotic tissue. Postoperatively, methicillin-resistant Staphylococcus aureus (MRSA) was identified, necessitating individualized, pharmacokinetically guided vancomycin therapy. This case highlights the importance of early vascular assessment following pediatric blunt trauma, the feasibility of autologous tissue reconstruction in infected arterial injuries, and the critical role of real-time therapeutic drug monitoring in optimizing the management of severe pediatric MRSA infections. This case underscores the need for multidisciplinary coordination and long-term follow-up to optimize outcomes in rare pediatric vascular trauma.